Pengarsipan Dokumen Akreditasi Sekolah Menggunakan Penerapan Finite State Automata - Adinda Nurkhalifah Akbal; Rachmat Julianto; Sevhia Khoirun Nisa; Aries Saifudin (Shofanah Media Berkah, 2023)
Archiving school accreditation documents is an important process in maintaining and managing track records and information relevant to a school's accreditation. However, often the filing process is still done manually and less efficiently. Therefore, this study aims to implement the application of Finite State Automata in archiving school accreditation documents to improve efficiency and regularity in managing these documents. In this research, we designed and developed a filing system that uses the Finite State Automata concept to classify, store, and search school accreditation documents based on certain categories and attributes. This method enables the use of state-based rules that automatically set up archiving flows and processes. The test results show that the application of Finite State Automata in archiving school accreditation documents provides more efficient and accurate results, and makes it easier for users to find the required documents. It is hoped that this research can be a foundation for improving the management of school accreditation documents more systematically and effectively.